Study of the transition between capacitive and inductive modes on propanethiol plasma polymer properties: correlation between plasma and film chemistry - Thiry, Damien; Britun, Nikolay; Konstantinidis, Stephanos; Dauchot, Jean-Pierre; Guillaume, Maxime; Cornil, Jérôme; Rony Snyders, Rony (International Conference on Plasma Surface Engineering, 2013)
Not available